Kajian Perbandingan Teknik-Teknik Steganografi Ke Atas Pelaksanaan Penyembunyian Maklumat Dalam Persekitaran Imej - Hanafi, Mamat (2003)
The purpose of this study is to see the assessment of steganography techniques in implementation of information hiding process in image environment. The image format will be considered in this study are BMP, GIF, JPEG and TIFF. Three technique of steganography selected to be compared is Least Significant Bits (LSB), Masking & Filtering, and Algorithms & Transformations. This study based on research from researchers that has been done in ten years (1993 -2003). Further comparison made by looking to the aspect of advantages and disadvantages of each technique which summarized in the form of risk analysis (high risk, medium and low). The result from the comparison of risk for every technique above will be made as a guideline for the process of information concealment by using the techniques of steganography so that the process will become more efficient and effective.